HUBUNGAN KEBIASAAN POSISI TIDUR DENGAN RESIKO TERJADINYA SERANGAN ULANG PADA PASIEN PENYAKIT JANTUNG KORONER DI POLI JANTUNG RSUD GAMBIRAN KOTA KEDIRI - Joko Sutrisno (Universitas STRADA Indonesia, 2013)
Coronary Heart Disease is a condition where there is narrowing of the coronary blood vessels that disrupts blood flow to the heart muscle and heart muscle is damaged or malfunctioning. To prevent the occurrence of coronary heart disease, one of which is the heart of the Sleep Position Habits . Sim dextra the sleep position is heart of the sleep habits so as not to burden the heart’s performance and to help the renovation of heart function. Purpose of the study to determine the relationship of sleep position habits with risk of repeated attacks in patients with coronary heart disease in the heart poly Gambiran Hospital Kediri. In this study, researchers used a research design of Study Correlation with Cross Sectional approach. Statistical analysis of test data using Spearman Rho test with degrees of significance α <0.05. The study population was all patients coronary heart disease in the heart poly Gambiran Hospital Kediri. Consecutive sampling techniques using sampling obtained in accordance with inclusion criteria were 20 people. Independent variables in this study is the sleep position habits of coronary heart disease patients. and the dependent variable is the risk of repeated attacks in patients with coronary heart disease in the heart poly Gambiran Hospital Kediri. Data obtained from the results of the study sleep position habits on coronary heart disease patients is still largely not true that 55% (11 people). The risk of repeated attacks in patients with coronary heart disease most patients have a high risk for the occurrence of repeated attacks, as many as 60% (12 people).a significant Correlation of sleep position habits with risk of repeated attacks in patients with coronary heart disease in the heart poly Gambiran Hospital Kediri denganl Spearman Rho test statistic values obtained. Sig. (2-tailed) at p = 0.000 > α = 0.05 means that Ho received. The are necessarily the patients had a Sleep position right habits can reduce the risk of repeated attacks of coronary heart disease, repeated attacks can occur when and where aja can be caused by various factors, such as lack of activity, kebisaaan smoking, lifestyle, heredity.